Prevalence and Determinants of Refractive Errors among School Children of 5th -10th Standard: A Study from South Kerala - Vincy Nelson; Girija Viswanathan; Sony Simon (Medsci Publications, 2018)
Introduction: Refractive Error is an avoidable cause of visual im- pairment. Treatment of refractive errors is perhaps the simplest and effective forms of eye care. Objectives: This study was carried out to assess the prevalence and determinants of refractive errors among school children of 5th- 10th standard. Materials& Methods: Study Design: cross sectional study Sam- pling technique: stratified random sampling. Study participants: A total of 1020 students were included in the study.510 students from each school. All students were screened for defective vision with the help of Snellen‟s chart and optometrist confirmed the findings. Data was analysed to find the prevalence of refractive er- rors and also to find the determinants using percentages and chi- square tests. Results: 21.7% of students were found to have refractive errors. Children residing in the urban area(24.6%) were found to have more refractive errors compared to children residing in rural area(18.6%).Family history of refractive error was significantly as- sociated with prevalence of refractive errors.(p<0.001). Conclusion: Boys were having higher prevalence of refractive er- rors compared to girls. Myopia was the most common form of re- fractive error. Regular eye screening should be done in school level. IEC activities should play a major role in eye health.